2007
DOI: 10.1186/1471-244x-7-37
|View full text |Cite
|
Sign up to set email alerts
|

Five-factor model personality traits in opioid dependence

Abstract: Background: Personality traits may form a part of the aetiology of opioid dependence. For instance, opioid dependence may result from self-medication in emotionally unstable individuals, or from experimenting with drugs in sensation seekers. The five factor model (FFM) has obtained a central position in contemporary personality trait theory. The five factors are: Neuroticism, Extraversion, Openness to Experience, Agreeableness and Conscientiousness. Few studies have examined whether there is a distinct persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
58
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 48 publications
15
58
0
4
Order By: Relevance
“…Alternatively, one might speculate that a personality profile characterized by low Openness and/or low Conscientiousness is not specific to GD, but rather associated to addictions in general. In particular, while a meta-analysis by Kotov and colleagues (2010) found Openness to be largely unrelated to SUD and other mental disorders, other studies have repeatedly found low Conscientiousness scores to be associated with drugs and alcohol use (Flory, Lynam, Milich, Leukefeld, & Clayton, 2002;Grekin, Sher, & Wood, 2006;Kornør & Nordvik, 2007;E. D. Martin & Sher, 1994;Terracciano, Löckenhoff, Crum, Bienvenu, & Costa, 2008;Trull & Sher, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, one might speculate that a personality profile characterized by low Openness and/or low Conscientiousness is not specific to GD, but rather associated to addictions in general. In particular, while a meta-analysis by Kotov and colleagues (2010) found Openness to be largely unrelated to SUD and other mental disorders, other studies have repeatedly found low Conscientiousness scores to be associated with drugs and alcohol use (Flory, Lynam, Milich, Leukefeld, & Clayton, 2002;Grekin, Sher, & Wood, 2006;Kornør & Nordvik, 2007;E. D. Martin & Sher, 1994;Terracciano, Löckenhoff, Crum, Bienvenu, & Costa, 2008;Trull & Sher, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…Negative affectivity is associated with higher vulnerability to stress, more intense emotional reactions in daily situations, and a tendency to use intoxicating substances, including alcohol, when confronted with stress (8)(9)(10). To date, only a few smaller studies have investigated the association between negative affectivity and alcohol use in pregnancy, with inconsistent results.…”
Section: Key Messagementioning
confidence: 99%
“…From a biomedical perspective, health could be linked to possible personal traits in opioid dependency, as recently shown by Kornor and Nordvik (2007). They found differences between the opioid-dependent group and the matched comparison group, suggesting that the personality traits of people with opioid dependence are different from their non-clinical peers.…”
Section: Healthmentioning
confidence: 92%